2013
DOI: 10.12693/aphyspola.123.371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Precipitation Method on Properties of Hydroxyapatite Powders

Abstract: The aim of this study was the compare the properties of hydroxyapatite as a function of two dierent methods (chemical and biomimetic precipitation). Powder products were called as chemical hydroxyapatite for chemical method and biomimetic hydroxyapatite for biomimetic method. Precipitated powders with both methods were characterized by Fourier transform infrared, X-ray diraction, X-ray uorescence and measurements of hardness and density. Chemical analysis results showed that dried-biomimetic hydroxyapatite sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The absorbed and occluded water, representing the typical bands of OHgroups were detected at about 3445.66 cm −1 and 1640.18 cm −1 , correspondingly. Similar trend of typical bands of PO4 3and OHgroups were reported in the literature [19,20]. 6 Key Engineering Materials IX possess pore sizes of about 275 µm while SCHA+Mg(OH) 2 scaffolds have relatively larger pore sizes of approximately 363 µm; both scaffolds showed appropriate pore size range of ideal scaffolds for bone tissue engineering (200-500 µm).…”
Section: Resultssupporting
confidence: 80%
“…The absorbed and occluded water, representing the typical bands of OHgroups were detected at about 3445.66 cm −1 and 1640.18 cm −1 , correspondingly. Similar trend of typical bands of PO4 3and OHgroups were reported in the literature [19,20]. 6 Key Engineering Materials IX possess pore sizes of about 275 µm while SCHA+Mg(OH) 2 scaffolds have relatively larger pore sizes of approximately 363 µm; both scaffolds showed appropriate pore size range of ideal scaffolds for bone tissue engineering (200-500 µm).…”
Section: Resultssupporting
confidence: 80%
“…• C and the formation of new phases such us: hibonite CA 6 and β-TCP at low temperature and CA 6 and CA 2 at high temperature.…”
Section: Resultsmentioning
confidence: 99%
“…However, the principal limitation of these materials is that has low fracture strength, low toughness and poor fatigue resistance, which restricts the clinical orthopedic and dental applications [3,4]. The incorporation of a ceramic second phase dispersed in a ceramic matrix is known to improve the mechanical properties [5,6]. HA and β-TCP materials must be reinforced by alumina, because it is also classified as a bioinert material.…”
Section: Introductionmentioning
confidence: 99%
“…2) illustrated that all sintered scaffolds exhibited the characteristic bands located at about 465-475 cm -1 (v2), 550-570 and 600-609 cm -1 (v4), 960-966 cm -1 (v1), and 1020-1120 cm -1 (v3) are attributed to phosphate (PO4 3-) groups in the apatite structure [30], [32]. The typical bands of the stretching modes for hydroxyl (OH -) groups were detected at around 3400-3600 cm -1 (absorbed water) and 1600-1700 cm -1 (occluded water) [33], [34]. The results obtained thus far showed that there is no evidence of FTIR spectra disrupted with the addition of the controllable amount of divalent cation dopants (Mg 2+ , Co 2+ and Sr 2+ ) either in the binary or ternary CHA.…”
Section: Scaffold Characterizationmentioning
confidence: 98%